Prairie wetland communities recover at different rates following hydrological restoration. (November 2016) - Bortolotti, Lauren E.; Vinebrooke, Rolf D.; St. Louis, Vincent L.
Summary: Prairie pothole wetlands provide many ecosystem services, including supporting biodiversity and filtering water on the landscape. However, over half of these wetlands have been drained for agriculture, thereby requiring restoration to re‐establish ecosystem services. We assessed the recovery of hydrologically restored wetlands based on water chemistry and taxonomic shifts within and across five biological communities (phytoplankton, benthic diatoms, zooplankton, macroinvertebrates, submersed aquatic vegetation [SAV]). We sampled 24 wetlands in southeastern Saskatchewan, Canada, spanning three restoration states: recently restored (restored 1–3 years before the study; n  =   8), older restored (restored 7–14 years before the study; n  =   8) and natural (never drained; n  =   8). Within approximately a decade of the re‐establishment of these previously drained wetlands, water chemistry, macroinvertebrate and SAV communities closely resembled those in natural wetlands. Here, total phosphorus and carbon dioxide concentrations declined, while salinity and pH increased, with time since restoration. No detectable differences in diatom and zooplankton communities persisted among the restored and natural sites; however, cyanobacteria were more representative of the restored wetlands Our findings suggest that hydrological restoration is an effective tool for re‐establishing baseline water quality and the capacity of prairie wetlands to support biodiversity across multiple trophic levels. However, given that there is a decadal lag in the re‐establishment of certain species, it is preferable to protect and retain intact wetlands on the landscape.